A systematic review of questionnaires measuring asthma control in children in a primary care population - Bousema, Sara; Bohnen, Arthur M.; Bindels, Patrick J. E.; Elshout, Gijs (NPJ primary care respiratory medicine, 2023)
Several questionnaires are used to measure asthma control in children. The most appropriate tool for use in primary care is not defined. In this systematic review, we evaluated questionnaires used to measure asthma control in children in primary care and determined their usefulness in asthma management. Searches were performed in the MEDLINE, Embase, Web of Science, Google Scholar and Cochrane databases with end date 24 June 2022. The study population comprised children aged 5–18 years with asthma. Three reviewers independently screened studies and extracted data. The methodological quality of the studies was assessed, using the COSMIN criteria for the measurement properties of health status questionnaires. Studies conducted in primary care were included if a minimum of two questionnaires were compared. Studies in secondary or tertiary care and studies of quality-of-life questionnaires were excluded. Heterogeneity precluded meta-analysis. Five publications were included: four observational studies and one sub-study of a randomized controlled trial. A total of 806 children were included (aged 5–18 years). We evaluated the Asthma Control Test (ACT), childhood Asthma Control Test (c-ACT), Asthma APGAR system, NAEPP criteria and Royal College of Physicians’ ‘3 questions’ (RCP3Q). These questionnaires assess different symptoms and domains. The quality of most of the studies was rated ‘intermediate’ or ‘poor’. The majority of the evaluated questionnaires do not show substantial agreement with one another, which makes a comparison challenging. Based on the current review, we suggest that the Asthma APGAR system seems promising as a questionnaire for determining asthma control in children in primary care.